Political Tolerance and Social-Political Culture as the Factors of Formation the Person’s Professionalism and the Students’ Action – the Future European Teacher: Array - Boychev, Ivan; Tsokur, Оlga (Journal of Danubian Studies and Research, 2020)
The article deals with the problem of foundation of necessity of the single-minded formation of the political tolerance and cultivating the European person as the factors of developing the Personal professionalism and tolerance of European Teacher. It’s analised as a social norm which is regulated by social and mutual action with other participants of the pedagogical process as the character of educational policy who is from one social group or from other political cultures and are ready to respect the politician opponent. They are ready to understand the necessity of existence the different political forces, systems, orientations, directions, values, norms, models of political behaviour. The development of the students’ socio-political culture as the European-Teacher that means the definite stereotypes of political mentality and behaviour to the person reflect the democratic mechanisms and ways of their attitude to Power and its realization. All above mentioned are foreseen the fundamental study of the political component in the Process of education in modern University. The gender is the main component which reflects the Students’ political tolerance and culture, educational and economic capital the family where they were born and brought up, religious identity, social and political practice and social communication with the members of the first and the second socialization. We name such components of abovementioned phenomenon as the Family Institution, Education, Religion, publicpolitical societies and the Mass-media.